Research on Regenerative Braking Algorithm for New Energy Vehicles - Su, Jintao; Lou, Jianping; Jiang, Xiaolu (IOP conference series. Earth and environmental science, 2021)
This paper introduces the research status of regenerative braking abroad, expounds the typical regenerative braking algorithm, and introduces the overall structure of the integrated control algorithm of regenerative braking and stability. By comparing regenerative braking and ESP coordinated control algorithm, ABS and ESP coordinated control algorithm and dynamic coordinated control algorithm, the theoretical limitations, advantages and disadvantages of typical regenerative braking algorithm are discussed. It provides material for studying regenerative braking algorithm.